Perceived Effects of Climate change on Farmer’s Livelihood in North Western Nigeria - Idris, Amina Aminu; Abdullahi, Ali; Daneji, Mahmud Ibrahim; Suleiman, Muhammad Sabiu; Sani, Sufiyyanu; Nasiru, Aminu (International Journal of Environment, Agriculture and Biotechnology, 2024)
Northwestern Nigeria has been identified as one of the most vulnerable regions to climate change in Nigeria. The study assessed the perceived effects of climate change on the farmer’s livelihood. This study employed a combination of qualitative and quantitative analytical methods. Multi-stage sampling technique was used to select four local government areas (LGAs) from Kano State and random selection of 260 farmers from 52 cooperatives within these LGAs. The collected data were analysed appropriately to achieve the objectives of the results. The results indicate that 57.7% were aware of climate change and understood it through patterns of rainfall, temperature, and changes in yield. The majority of the farmers (84.2%) believed that climate change was responsible for an increase in the rate of diseases among the family members in the area and an increase in the distance travelled in search of drinking water. A reasonable percentage of farmers (62.7%) believed that the main road was eroding, making it difficult to get to the market, schools, and health centers. To cope with climate change, farmers used climate-sensitive varieties and crop diversification. In conclusion, climate change has had a real impact on resources like agriculture, water availability, family health, roads, and social networks. Therefore, we recommend providing farmers with technical training on the consequences of climate change and coping strategies.